Ejection fraction estimation using deep semantic segmentation neural network on 2D Echocardiography data - Khan, Abde Musavvir; Shejuty, Myesha Farid; Talukder, MD. Nafis Shariar; Zubayear, Syed Ibna (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.